Limited production of sulfate and nitrate on front-associated dust storm particles moving from desert to distant populated areas in northwestern China - F. Wu (Atmospheric Chemistry and Physics, 2017)
Sulfate and nitrate compounds can greatly increase the hygroscopicity of mineral particles in the atmosphere and consequently alter the particles' physical and chemical properties. Their uptake on long-distance-transported Asian dust particles within mainland China has been reported to be substantial in previous studies, but the production was very inefficient in other studies. We compared these two salts in particles collected from a synoptic-scale, mid-latitude, cyclone-induced dust storm plume at the Tengger Desert (38.79° N, 105.38° E) and in particles collected in a postfrontal dust plume at an urban site in Xi'an (34.22° N, 108.87° E) when a front-associated dust storm from the Tengger Desert arrived there approximately 700 km downwind. The results showed that the sulfate concentration was not considerably different at the two sites, while the nitrate concentration was slightly larger at the urban site than that at the desert site. The estimated nitrate production rate was 4–5 ng µg−1 of mineral dust per day, which was much less than that in polluted urban air. The adiabatic process of the dust-loading air was suggested to be the reason for the absence of sulfate formation, and the uptake of background HNO3 was suggested to be the reason for the small nitrate production. According to our investigation of the published literature, the significant sulfate and nitrate in dust-storm-associated samples within the continental atmosphere reported in previous studies cannot be confirmed as actually produced on desert dust particles; the contribution from locally emitted and urban mineral particles or from soil-derived sulfate was likely substantial because the weather conditions in those studies indicated that the collection of the samples was started before dust arrival, or the air from which the samples were collected was a mixture of desert dust and locally emitted mineral particles. These results suggest that the production of nitrate and sulfate on dust particles following cold fronts is likely limited when the particles move from the desert to populated areas within the continent. For an accurate quantification of sulfate and nitrate formed on long-distance-transported desert dust particles at downwind populated areas in eastern China, dust collection efforts are indispensable to minimize any possible influence by locally emitted particles or at least to ensure that the samples are collected after dust arrival.